Inventory of Ficus Species in The Bukit Manjai Valley Tropical Rainforest Biodiversity Park Area - Aprillita, Gina; Widiyastuti, Dewi Amelia; Nurtamara, Luthfiana; Rezeki, Amalia (Jurnal Biologi Tropis, 2025)
The Bukit Manjai Valley Tropical Rainforest Park is home to an abundance of plants that includes a host of Ficus species. The objective of this study was to inventory and descriptively account for the Ficus present in the park. The purposive sampling method was used, where any time we found a Ficus plant, the data collection occurred. Upon finding a Ficus plant, we documented it with photographic evidence and provide scientific identification along with measurements for environmental parameters including air temperature, air humidity (RH), light intensity, soil pH, altitude elevation, soil moisture, and wind speed. The study identified five species of Ficus, specifically, Ficus fistulosa Reinw. Ex Blume, Ficus montana Burm.f., Ficus rosulata C.C.Berg, Ficus uncinata (King) Becc and, Ficus variegata Blume. The study results suggest that the environmental conditions in Bukit Manjai Valley Tropical Rainforest Park, are very conducive for the growth and survival of a variety of Ficus species. This inventory study provides important information to aid the understanding of biodiversity, especially of the Ficus genus, in the tropical rainforest ecosystem of Borneo.